Improvement in liver steatosis after the switch from a ritonavir-boosted protease inhibitor to raltegravir in HIV-infected patients with non-alcoholic fatty liver disease. Issue 8 (3rd August 2019) - Calza, Leonardo; Colangeli, Vincenzo; Borderi, Marco; Coladonato, Simona; Tazza, Beatrice; Fornaro, Giacomo; Badia, Lorenzo; Guardigni, Viola; Verucchi, Gabriella; Viale, Pierluigi
Abstract: Background: The ritonavir-boosted protease inhibitor (PI/r) use has been associated with several metabolic abnormalities, and the non-alcoholic fatty liver disease (NAFLD) is becoming a very frequent comorbidity among HIV-infected patients. Methods: We performed an observational, prospective study of HIV-infected patients with NAFLD, receiving one PI/r plus two nucleoside analogues, who switched from the PI/r to raltegravir or were treated only with lifestyle modification, maintaining antiretroviral therapy unchanged. Changes in liver steatosis after 12 months were evaluated by transient elastography and measurement of controlled attenuation parameter (CAP). Results: As a whole, 61 patients (46 males; median age, 55.4 years) were enrolled, and 32 of them have been switched from PI/r to raltegravir. At baseline, median CAP was 259 dB/m, 28 (45.9%) subjects had a moderate-to-severe hepatic steatosis (CAP ≥260 dB/m), and 19 patients (31.1%) had elevated aminotransferases. Type-2 diabetes mellitus was present in 5 persons, and chronic HCV coinfection in 4. At month 12, the median decrease in CAP values was -27 dB/m in patients switched to raltegravir and -11 dB/m in those with unchanged cART ( p  = .021). The number of patients with CAP ≥260 dB/m decreased from 16 to 6 (-62.5%) in patients switched to raltegravir and from 12 to 8 (−33.3%) in the other group ( p  = .037). Conclusion: After 12 months, HIV-infected patients with NAFLD switching from a PI/r to raltegravir showed a significantly greater decrease in the hepatic steatosis degreee in comparison with those with unchanged cART and treated only with lifestyle modification.